First report of pteridocolous discomycetes, Lachnum lanariceps and L. oncospermatum, on decayed tree fern in Bukit Bendera (Penang Hill), Pulau Pinang, Malaysia - Razikin, Muhammad Zulfa Mohd; Nagao, Hideyuki; Zakaria, Rahmad (Prince of Songkla University, 2014)
Bukit Bendera is 833 m above sea level and situated in the Northern part of Penang Island, Malaysia. Generally an average temperature is between 20 to 27°C, which is about 5°C cooler than at the sea level. The hill dipterocarp forest dominates Bukit Bendera and tree fern scatteredly grows at higher altitude. Two Lachnum spp. were observed as pteridocolous cup fungi on decayed rachides of several tree fern species, Cyathea contaminans, C. latebrosa, and C. hymenodes. Lachnum oncospermatum is characterized by a wrinkled apothecium and branched stipe. The hairs contain brown colored resinous materials and are finely granulated. Lachnum lanariceps is characterized by a central and cylindrical stipe and hairs containing pale yellow pigment with red or garnet resinous matter. These two Lachnum species are new to Malaysia.